When Emotions Matter: Focusing on Emotion Improves Working Memory Updating in Older Adults - Berger, Natalie; Richards, Anne; Davelaar, Eddy J. (Frontiers in Psychology, 2017)
Research indicates that emotion can affect the ability to update and monitor content in working memory, an executive function that is usually referred to as updating. However, it is less clear if the effects of emotion on updating vary with its relevance for the task and with age. Here, 25 younger (20 – 34 years of age) and 25 older adults (63 – 80 years of age) performed a 1-back and a 2-back task, in which they responded to younger, middle-aged, and older faces showing neutral, happy or angry expressions. The relevance of emotion for the task was manipulated through instructions to make match/non-match judgments based on the emotion (i.e., emotion was task-relevant) or the age (i.e., emotion was task-irrelevant) of the face. It was found that only older adults updated emotional faces more readily compared to neutral faces as evidenced by faster RTs on non-match trials. This emotion benefit was observed under low-load conditions (1-back task) but not under high-load conditions (2-back task) and only if emotion was task-relevant. In contrast, task-irrelevant emotion did not impair updating performance in either age group. These findings suggest that older adults can benefit from task-relevant emotional information to a greater extent than younger adults when sufficient cognitive resources are available. They also highlight that emotional processing can buffer age-related decline in WM tasks that require not only maintenance but also manipulation of material.